Case report: a novel deep intronic splice-altering variant in DMD as a cause of Becker muscular dystrophy - Berntsson, Shala Ghaderi; Matsson, Hans; Kristoffersson, Anna; Niemelä, Valter; van Duyvenvoorde, Hermine A.; Richel-van Assenbergh, Cindy; van der Klift, Heleen M.; Casar-Borota, Olivera; Frykholm, Carina; Landtblom, Anne-Marie (Frontiers in Genetics, 2023)
We present the case of a male patient who was ultimately diagnosed with Becker muscular dystrophy (BMD; MIM# 300376) after the onset of muscle weakness in his teens progressively led to significant walking difficulties in his twenties. A genetic diagnosis was pursued but initial investigation revealed no aberrations in the dystrophin gene (DMD), although immunohistochemistry and Western blot analysis suggested the diagnosis of dystrophinopathy.Eventually, after more than ten years, an RNA analysis captured abnormal splicing where 154 nucleotides from intron 43 were inserted between exon 43 and 44 resulting in a frameshift and a premature stop codon. Normal splicing of the DMD gene was also observed. Additionally, a novel variant c.6291-13537A>G in DMD was confirmed in the genomic DNA of the patient.The predicted function of the variant aligns with the mRNA results. To conclude, we here demonstrate that mRNA analysis can guide the diagnosis of non-coding genetic variants in DMD.